2021
DOI: 10.21037/qims-20-1212
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of non-contact anterior cruciate ligament injury as determined by bone contusion location and severity

Abstract: Background: The location and severity of tibiofemoral bone contusions in magnetic resonance imaging scans in patients with acute non-contact anterior cruciate ligament injuries can reflect the primary mechanisms of anterior cruciate ligament injuries. There has been limited investigation to subdividing the bone contusion model in the medial and lateral directions of the tibial plateau and the femoral condyle.Methods: A retrospective review of 93 consecutive magnetic resonance imaging examinations of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…In line with previous reports [ 22 , 23 , 25 , 27 ], our results show that combined central lateral femoral condyle and posterior lateral tibial plateau BB pattern to be the result of indirect ACL injury mechanism in 100% of cases, and was the primary or typical BB pattern accounting for 58% of the included footballers. Identifying this initial pattern in patients undergoing ACL reconstruction surgery may have a potential role in guiding footballers' rehabilitation, focusing on valgus knee collapse prevention exercises and improving cutting task biomechanics, and recognizing individuals at higher risk of reinjury.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous reports [ 22 , 23 , 25 , 27 ], our results show that combined central lateral femoral condyle and posterior lateral tibial plateau BB pattern to be the result of indirect ACL injury mechanism in 100% of cases, and was the primary or typical BB pattern accounting for 58% of the included footballers. Identifying this initial pattern in patients undergoing ACL reconstruction surgery may have a potential role in guiding footballers' rehabilitation, focusing on valgus knee collapse prevention exercises and improving cutting task biomechanics, and recognizing individuals at higher risk of reinjury.…”
Section: Discussionsupporting
confidence: 92%
“…Kim-Wang et al, in a cross-sectional study comprising 136 patients undergoing ACL reconstruction, found medial compartment BB in 72% of patients in his series and the presence of 3 or 4 contusions in 65% of them, with a prevalence of 35% involving all compartments [ 16 ]. Similarly, Qiu et al, in a retrospective analysis of 93 patients with an ACL injury, reported medial tibial plateau involvement in 69.8% and medial femoral condyle BB in 49.4% of patients [ 23 ]. Although medial compartment-only patterns represented only 5.3% of patients, four contusion patterns were the most common, accounting for 36.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have long been suspected as a risk predictor for worse outcomes following ACL injury [ 30 ], although to our knowledge, no data on this association has been published. Qiu et al [ 31 ] performed a retrospective study by analyzing 93 MRI images of patients who had suffered an acute non-contact ACL injury to identify bony contusions of the knee by MRI scans for each anatomic femoral and tibial joint site. They found a prevalence of bone contusions of 78.49% at the lateral femoral condyle, 88.17% at the lateral tibial plateau, 49.46% at the medial femoral condyle, and 69.89% at the medial tibial plateau; determining that the location patterns and severity of bone contusions in patients indicated that tibial internal rotation, valgus, and anterior and lateral tibial translation were the main mechanisms of non-contact ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In contrast, more than 70% of ACL injuries occur in a noncontact manner, during which rapid movement that confers supraphysiological stresses, such as changing directions, landing, deceleration, or pivoting, can lead to rupture of the ACL. 10,12 While the mechanisms of ACL injury have been thoroughly investigated, the underlying kinematic forces at the time of injury remain debated.…”
mentioning
confidence: 99%